GLUT1: A novel tool reflecting proliferative activity of lung neuroendocrine tumors?. Issue 1 (20th December 2016) - Benzerdjeb, Nazim; Berna, Pascal; Sevestre, Henri
Abstract : Lung neuroendocrine tumors (LNT) represents approximately 20% of all lung cancers. The classification of LNT relies upon morphology. Recently, in the World Health Organization (WHO) classification, Ki‐67 rate has been proposed for classification. It is, however, known that Ki‐67 count has a poor interlaboratory reproducibly. For that reason, our team has looked for a new biomarker. GLUT1 protein a facilitative glucose transporter protein which has ubiquitous expression in mammalian. GLUT1 is overexpressed in many human cancers. But, no study has evaluated the GLUT1 staining as an aid diagnosis in LNT. Our team have assessed the GLUT1 immunohistochemical staining in 36 LNT and to assess its diagnostic value. GLUT1 staining was higher in neuroendocrine carcinoma than in carcinoid tumor. A positive predictive value in a priori and posteriori testing for diagnosis of LNT is demonstrated. GLUT1 staining could aid in the diagnosis and should be validated in a large prospective cohort.